Repairing Effect of New Dexamethasone Nanoparticles in the Treatment of Acute Lung Injury and Cluster Nursing: New Dexamethasone Nanoparticles in the Treatment of Acute Lung Injury - Chen, Xiu; Zhang, Jianlan; Weng, Fangfang (Cellular and Molecular Biology, 2022)
The repairing effect of new dexamethasone nanoparticles in the treatment of acute lung injury was investigated in this study, as well as cluster nursing. In this study, new dexamethasone model drugs were prepared by the aqueous solvent diffusion method, such as anti-ICAM-I monoclonal antibody-modified anionic dexamethasone NLCs and anti-ICAM-I monoclonal antibody-modified cationic dexamethasone NLCs. Besides, the physical and chemical properties and repairing effects of cationic dexamethasone on acute lung injury were compared. A mouse model of acute lung injury was established, and the anti-inflammatory effect of dexamethasone was evaluated by intravenous injection of dexamethasone nanoparticles in the intervention group and normal healthy mice in the control group. A total of 100 patients with acute lung injury in Hai’an People’s Hospital Affiliated with Nantong University were selected, of which 50 cases were given cluster nursing intervention and the other 50 cases were taken as the control group. A human vascular endothelial cell line was applied to establish the model cells, and a model of inflammatory endothelial cells in acute lung injury was constructed using lipopolysaccharide stimulation, to verify the cytotoxicity of dexamethasone NLCs. It was found that the anion particle size was 250.12 ± 20.15 nm, the cationic particle size was 245.7 ± 2.1 nm; their Zeta potentials were -31 ± 0.5 mV and 38 ± 0.6 mV in turn; their encapsulation rates were 91% and 83%, respectively; the drug loading was 3.7% and 3.4% in sequence; the release lowest rate was 60%. The 50% lethal dose of anionic cells was higher than 600 g/mL, while that of cationic cells was lower. The respiratory function of the cluster nursing intervention group was better markedly than that of the control group, and the lung infection rate was 2.5% in the intervention group and 15% in the control group. In conclusion, dexamethasone nanoparticles had good anti-inflammatory effects. Anionic ICAM NLCs were less toxic than cationic cells and could better bind to lung vascular endothelial cells, which might reduce adverse drug reactions. Therefore, the building of bundled nursing could effectively alleviate respiratory dysfunction and reduce the infection rate of patients.